P1_2 Unmanned Aerial Vehicles - Botterill, Sarah; Comber, Emma; James, Matt; Spence, Dan (Physics Special Topics, 2011)
In this article, we estimate the energy required for a sustained flight of 11.98 hours for a UAV (modelled on the in-development BAE Taranis) from London, United Kingdom to Baghdad, Iraq, and the amount of fuel needed for the journey. Approximations are made as to the physical parameters of the UAV, taking those known for similar-sized aircraft. We find that the energy consumption would be 30 + 0.5 GJ, equating to approximately 698 kg of aviation fuel.